FOREIGN EXPERIENCE OF STATE REGULATING IN THE FIELD OF ENVIRONMENTAL PROTECTION - Bokovykova Yu.V.; Panova O.V. (Pressing Problems of Public Administration, 2018)
The experience of developed countries in the  eld of state regulation in the  eld of environmental protection has been analyzed. Effective modern regulatory instruments in the  eld of environmental protection have been dedicated. The conditions under which the use of foreign experience in Ukraine is possible have been determined.